Pengetahuan dan Sikap Masyarakat dalam Upaya Pencegahan Penyakit Tuberkulosis Paru: Tinjauan Pustaka - Radandima, Ester; Toru, Veronika; Mila, Antonetha R H (Poltekkes Kemenkes Kupang, 2022)
Background: Pulmonary Tuberculosis is a major cause of death in most countries in the world. Lack of information obtained by the public can affect public knowledge in making efforts to prevent the transmission of pulmonary tuberculosis. If this is left unchecked, it will have a bad impact in the form of increasingly widespread transmission of pulmonary tuberculosis and increasing morbidity rates resulting in increased deaths. Objective: to determine community knowledge and attitudes in efforts to prevent pulmonary TB disease. Method: The research used a literature review with problem identification stages, data search using the Google Scholar database with the keywords